Oxidation of lignin and lignin β-O-4 model compounds via activated dimethyl sulfoxide. Issue 127 (14th December 2015) - Mobley, Justin K.; Yao, Soledad G.; Crocker, Mark; Meier, Mark
Abstract : Oxidation of lignin and β-O-4 models using activated DMSO compounds can give ketones or enol ethers. Abstract : Lignin oxidation reactions are increasingly being utilized in the field of lignin valorization. This is primarily due to the prospect of obtaining high-value aromatic products from cleavage of the Cα –Cβ bond in lignin's β-O-4 linkages. In this work activated dimethyl sulfoxide reactions, namely Swern and Parikh–Doering oxidations, were performed both on lignin and on compounds modeling the β-O-4 linkage. When phenolic moieties were present in the model compounds, enol ethers were formed rather than the ketone expected from oxidation of the β-O-4 alcohol moiety. Conversely, in the absence of phenolic moieties, the β-O-4 alcohol was oxidized to a ketone. These results are interpreted in terms of enol ether formation from a quinone methide intermediate formed via deprotonation of the phenolic –OH in the initial sulfur ylide species. When applied to Kraft lignin, alcohol oxidation was observed at both the α and γ positions in lignin under both Swern and Parikh–Doering conditions, although analytical data were unable to shed light on the relative importance of enol ether versus 1, 3-diketone formation (or its tautomer). These results emphasize the importance of working with realistic lignin model compounds in order to understand and develop lignin chemistry.